Next-generation cognitive radar systems - Mishra, Kumar Vijay; Shankar M. R., Bhavani; Rangaswamy, Muralidhar (Radar, sonar and navigation, 2023)
Next-Generation Cognitive Radar Systems brings together contributions from leading researchers who are engaged in the research and development of next generation cognitive abilities in radar engineering. It features recent advances in the theory and applications of advanced Cognitive Radar (CR) tools and examines emerging challenges. The chapters include mathematical and computational methods to combat important CR challenges as well as the applications of recent theories and algorithms to various applied CR aspects. The book is intended to be used as a supplementary text for first-level graduate courses on radar theory and systems, radar signal processing, detection and estimation theory, and array signal processing. The book can also be used as a main textbook for upper-level graduate courses such as advanced topics in electromagnetics, advanced topics in radar, rf and communications, and contemporary topics in signal processing and optimization.